2018
DOI: 10.1186/s13071-017-2531-8
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of the filarial and Leishmania co-endemicity in two ecologically distinct settings in Mali

Abstract: BackgroundFilariasis and leishmaniasis are two neglected tropical diseases in Mali. Due to distribution and associated clinical features, both diseases are of concern to public health. The goal of this study was to determine the prevalence of co-infection with filarial (Wuchereria bancrofti and Mansonella perstans) and Leishmania major parasites in two ecologically distinct areas of Mali, the Kolokani district (villages of Tieneguebougou and Bougoudiana) in North Sudan Savanna area, and the district of Kolondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…However, amplification of COX1 ruled out the possibility of infection or coinfection with D. immitis, D. repens, or Cercopithifilaria spp. Meanwhile, studies have revealed polyparasitism coinfection of W. bancrofti and L. donovani [4], W. bancrofti and M. perstans with malaria and L. major [60,61], as well as D. immitis, D. repens, A. dracunculoides, and L. infantum [6,7]. This agrees with our results since all dogs found to be positive by microscopy were positive for L. infantum through the amplification of a highly conserved C region of the hsp70 gene with six or seven hsp70-I copies and one hsp70-II copy [62,63] (Figure -4).…”
Section: Discussionmentioning
confidence: 99%
“…However, amplification of COX1 ruled out the possibility of infection or coinfection with D. immitis, D. repens, or Cercopithifilaria spp. Meanwhile, studies have revealed polyparasitism coinfection of W. bancrofti and L. donovani [4], W. bancrofti and M. perstans with malaria and L. major [60,61], as well as D. immitis, D. repens, A. dracunculoides, and L. infantum [6,7]. This agrees with our results since all dogs found to be positive by microscopy were positive for L. infantum through the amplification of a highly conserved C region of the hsp70 gene with six or seven hsp70-I copies and one hsp70-II copy [62,63] (Figure -4).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for a sequential relationship between LF or VL infection and development of clinical disease has previously not been shown, likewise the role of co-infection in disease pathology is not well understood. A study from Mali addressing the prevalence of filaria (by W. bancrofti immunochromatographic test (ICT)) and Leishmania infection (Leishmania skin test (LST) reaction to L. major infection) found slightly higher prevalence of LST positive reactions in ICT positive individuals [46]. While this study was too PLOS NEGLECTED TROPICAL DISEASES small to draw definitive conclusions, it, in line with the data presented here, suggest that further investigation on the role filarial co-infections have on concomitant diseases is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of filarial and leishmanial co-infections has been reported in some parts of the world [108]. In the co-infected mouse model, local immune responses to filarial and leishmanial infections were polarized and compartmentalized [109].…”
Section: Leishmaniasismentioning
confidence: 98%